Inhibitory activity of hibifolin on adenosine deaminase- experimental and molecular modeling study. (October 2016) - Arun, K.G.; Sharanya, C.S.; Sandeep, P.M.; Sadasivan, C.
Graphical abstract: Highlights: Adenosine deaminase inhibitors considered as drug leads against malignancies. Hibifoline, a flavonoid from Helicteres isora inhibits ADA. The free energy of binding is −7.21 Kcal/mol. In silico studies confirms the mode of binding. Abstract: Adenosine deaminase (ADA) is an enzyme involved in purine metabolism. ADA converts adenosine to inosine and liberates ammonia. Because of their critical role in the differentiation and maturation of cells, the regulation of ADA activity is considered as a potential therapeutic approach to prevent malignant and inflammatory disorders. In the present study, the inhibitory activity of a plant flavonoid, hibifolin on ADA is investigated using enzyme kinetic assay and isothermal titration calorimetry. The inhibitory constant of hibifolin was found to be 49.92 μM ± 3.98 and the mode of binding was reversible. Isothermal titration calorimetry showed that the compound binds ADA with binding energy of −7.21 Kcal/mol. The in silico modeling and docking studies showed that the bound ligand is stabilized by hydrogen bonds with active site residues of the enzyme. The study reveals that hibifolin can act as a potential inhibitor of ADA.